1)(1+Tanθ)/(1-tanθ)=(cotθ+1)/(cotθ-1)
证:(1+Tanθ)/(1-tanθ)
=[cotθ(1+Tanθ)]/[cotθ(1-tanθ)]
=(cotθ+1)/(cotθ-1)
2)1+2tan平方θ=sec四次方θ-tan四次方θ
证:sec^4θ-tan^4θ
=(1+tan²θ)²-(tan²θ)²
=(1+tan²θ-tan²θ)(1+tan²θ+tan²θ)
=1+2tan²θ
3)tan平方θ-sin平方θ=tan平方θsin平方θ
证:tan²θ-sin²θ
=tan²θ-cos²θtan²θ
=tan²θ(1-cos²θ)
=tan²θsin²θ
4)sin四次方θ-cos四次方θ+cos平方θ=sin平方θ
证:sin^4θ-cos^4θ+cos²θ
=(sin²θ-cos²θ)(sin²θ+cos²θ)+cos²θ
=sin²θ-cos²θ+cos²θ
=sin²θ
5)cot平方θ-cos平方θ=cos平方θcot平方θ
证:cot²θ-cos²θ
=cot²θ-cot²θsin²θ
=cot²θ(1-sin²θ)
=cot²θcos²θ
6)(cot平方θ+1)/(tan平方θ+1)=cot平方θ
证:(cot²θ+1)/(tan²θ+1)
=[cot²θ(cot²θ+1)]/[cot²θ(tan²θ+1)]
=[cot²θ(cot²θ+1)]/(1+cot²θ)
=cot²θ
7)(cscθ-cotθ)平方=(1-cosθ)/(1+cosθ)
证:(cscθ-cotθ)²
=(1/sinθ - cosθ/sinθ)²
=(1-cosθ)²/sin²θ
=(1-cosθ)²/(1-cos²θ)
=(1-cosθ)²/[(1-cosθ)(1+cosθ)]
=(1-cosθ)/(1+cosθ)
12)cos平方θ-sin平方θ=1-2sin平方θ
证:cos²θ-sin²θ
=(1-sin²θ)-sin²θ
=1-2sin²θ
13)(1-cosθ)/sinθ+sinθ/(1-cosθ)=2cscθ
证:(1-cosθ)/sinθ + sinθ/(1-cosθ)
=(1-cosθ)/sinθ + sin²θ/[sinθ(1-cosθ)]
=(1-cosθ)/sinθ + (1-cos²θ)/[sinθ(1-cosθ)]
=(1-cosθ)/sinθ + (1-cosθ)(1+cosθ)/[sinθ(1-cosθ)]
=(1-cosθ)/sinθ + (1+cosθ)/sinθ
=2/sinθ=2cscθ
17)(1-cot平方θ)/(1+cot平方θ)+2cos平方θ=1
证:(1-cot²θ)/(1+cot²θ)+2cos²θ
=(1-cot²θ)/(1+cot²θ)+ 2(1-sin²θ)
=(1-cot²θ)/(1+cot²θ) - 2/csc²θ +2
=(1-cot²θ)/(1+cot²θ) - 2/(1+cot²θ) +2
=(1-cot²θ-2)/(1+cot²θ) +2
=-1+2=1
18)(1-sinθ)/(1+sinθ)=(secθ-tanθ)平方
证:(secθ-tanθ)²
=(1/cosθ - sinθ/cosθ)²
=(1-sinθ)²/cos²θ
=(1-sinθ)²/(1-sin²θ)
=(1-sinθ)²/[(1-sinθ)(1+sinθ)]
=(1-sinθ)/(1+sinθ)